Monkeypox: New epidemic or fake news? Study of psychological and social factors associated with fake news attitudes of monkeypox in Italy - Nimbi, Filippo Maria; Giovanardi, Guido; Baiocco, Roberto; Tanzilli, Annalisa; Lingiardi, Vittorio (Frontiers in Psychology, 2023)
Objective: Starting from May 2022, a growing number of monkeypox cases have been identified in several countries in Europe and the US. To date, information on social reaction to the news circulating about monkeypox is limited. Assessing psychological and social elements related to the tendency to misinterpret monkeypox information is urgent and useful in setting up tailored education and prevention programs for specific populations. The present study aims to explore the association of selected psychological and social variables to monkeypox attitudes as fake news. Methods: Three hundred and thirty-three participants (212 women, 110 men, and 11 other genders) from the general Italian population completed nine self-report measures. Results: Results showed that people that were more likely to believe that monkeypox was a hoax were: older, heterosexual, politically conservative, and more religious. Moreoverm they were more likely to show more negative attitudes towards gay men, higher levels of sexual moralism, less knowledge and fear about monkeypox, no previous infections of COVID-19, lower number of COVID-19 vaccine doses, and being closer to no-vax theories. On the psychological side, participants that were more likely to believe that the monkeypox was a hoax were associated with lower levels of epistemic trust and order traits, with higher levels of epistemic mistrust, close-mindedness, and ability to process emotions. A full mediation model which explores the relationships between the main variables related to fake news attitudes towards monkeypox was tested, reporting good fit indices. Conclusions: Results from the current study could be helpful to improve the effectiveness of health communication, design targeted education, and support people to engage in healthier behaviors.